PEMBENTUKAN ENERGI YANG POTENSIAL YANG BERPUSAT PADA SISTEM HVAC ATAS TATA KELOLA UDARA STRUKTUR RUANG BANGUNAN PERKOTAAN DI KOTA PALEMBANG YANG DIPENGARUHI IKLIM CUACA - Martin Luther King; Muhammad Ali; Sukarmansyah .; Muhammad Iskandar Badil (Jurnal Turbulen, 2018)
Stringent ventilation regulations make the humidity problem more serious. In modern society, people spend most of their time in built environments. More attention has been paid to indoor air quality and indoor thermal comfort. Fresh air centered HVAC systems are necessary for almost all buildings. In this chapter, a quantitative analysis is provided for the energy expenses and possible savings in fresh air ventilation. More specifically, hot and humid climates like Palembang are selected as the calculating sample. Under such climates, moisture recovery is more important than sensible recovery. Keywords: Humidity,Fresh Air, indoor thermal, HVAC, Palembang Society